CMET-08. BRAIN METASTASES AS PRIMARY PRESENTATION OF SOLID TUMORS: A DESCRIPTIVE ANALYSIS OF THE NATIONAL CANCER DATABASE (NCDB). (5th November 2018) - Garcia, Catherine; Slone, Stacey; St Clair, William; Durbin, Eric; Pittman, Thomas; Lightner, Donita; Villano, John
Abstract: INTRODUCTION: Survival of cancer patients with brain metastases (BM) has increased with novel therapies. Previous analyses have focus on radiation treatment or predate novel systemic therapies that have improved survival outcomes. METHODS: We analyzed the National Cancer Database from 2010–2014, for all patients with metastatic disease to the brain to analyze patterns of care across the United States. RESULTS: 88, 459 cases were included. The majority of patients were male (51.7%), white (84.2%), and non-Hispanic (92.6%), with a median age of 65 years. The most common primary cancer sites included lung and upper airway cancer (82.5%), breast cancer (4.2%), skin cancer (3.5%), and gastrointestinal tumors (2.3%). Hepatobiliary cancer patients had a higher frequency of comorbidities (9.6% with a Charlson-Deyo score ≥3). Patients were more likely to be treated in community centers (64.0%) and lived in metropolitan areas (79.0%). Overall 72.6% received any form of radiation, 53.5% received radiation to the brain, 52.1% received chemotherapy, 2.3% received immunotherapy, and 13.3% underwent surgical procedure to distant metastatic site. The most common radiation modality was whole-brain radiation (58.4%), followed by stereotactic radiosurgery (11.6%), other (0.65), and brachytherapy (0.1%). The type of radiation was unknown in 2.0% of the patients. Radiation to the brain was more common in skin cancer (63.4%). The use of chemotherapy was significantly lower in patients with hepatobiliary cancer (34.2%). Immunotherapy was used in 2.3% of patients, mainly in melanoma (13.6%), and breast cancer (8.15%). Median survival for all cases was 5 months, and was significantly higher in male reproductive system cancer (16.3 months), and lower in hepatobiliary cancer (2.7 months). CONCLUSIONS: The increased survival of BM in the current era exceeds historical RTOG recursive partitioning analysis. Large scale data, such as NCDB, is essential for single tumor analysis with treatment and survival data, and provides a reference for future investigations.